Investigating the Apparent Conflict in the Verses of the Quran about Adulteress’ Verdict - abdol gabar zargoshnasab (پژوهش نامه معارف قرآنی, 2018)
This article refers to the apparent conflict between the second verse of the chapter of Al Nor surah about adultery with verses 15 and 16 of An-Nisa surah (a chapter in the Quran entitled ‘Women’). Verse 15 of the Surah An-Nisa states that women who commit adultery must be confined in their houses. Apparently, this verse contradicts the following verse (verse 16) which states that adulteress women must be harassed. Moreover, both these verses are inconsistent with the second verse of the Surah Al Nor (another chapter in the Quran entitled ‘The Light’) which asserts that adulteresses must be whipped. A solution must be sought to resolve these contradictions by scrutinizing the above-mentioned verses and asking for religious authorities’ viewpoints about this issue. In this regard, according to some religious scholars, verse 16 abrogates verse 15 in the Surah An-NISA, and according to some others verse two in the Surah Al-NOOR abrogates both the other two. In contrast, some great interpreters have negated any probability of abrogation in the three verses due to different topics discussed in them. In this study which has been carried out using a descriptive analytical method, the researchers came to the conclusion that abrogation has not taken place at all and, in fact, there would not be any need to solve the problem by raising the topic of abrogation.